THE FILM APPLICATION IN TEACHING SPANISH AS A FOREIGN LANGUAGE (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
In this paper, we analyzed the film application in the class of Spanish as a foreign language. Due to the fact that film has many advantages which make it adequate for didactic application, it can contribute to a more efficient teaching process. An authentical material in audiovisual format provides various language input and contextualized situations, on whose basis students develop different linguistic skills and competences. Thereby, the presence of a ludic element additionally contributes to student’s motivation. For a successful film application in the class, the most important thing is to select adequate film material, to organize class and make the accompanying activities. The purpose of the paper is to point out at the efficiency of film in teaching, as well as to point out at the need for paying more attention to film application in teaching Spanish as a foreign language in Serbia.
Keywords: film, Spanish as a foreign language, language skills and competencies, effective teaching